Elevated rate capability of sulfur wrapped with thin rGO layers for lithium–sulfur batteries. Issue 37 (25th March 2015) - Ahn, Wook; Lee, Dong Un; Song, Hoon Sub; Yeon, Sun-Hwa; Kim, Kwang-Bum; Chen, Zhongwei
Abstract : The sulfur nanoparticle wrapped with thin layer of graphene is successfully synthesized by a facile solution impregnation method. Abstract : Sulfur–rGO composite is prepared by a facile solution method using carbon disulfide solvent as a cathode electrode material for lithium–sulfur batteries to investigate its electrochemical performance. The initial capacity of the sulfur–rGO composite is 1385 mA h g −1 obtained at 0.1 C-rate with an excellent average capacity reduction ratio of 0.37% per cycle (from 10 th to 100 th cycles).